MOF-DNA composite material, preparation method and application

By compounding the organic framework structure of metal-porphyrin derivatives with G-DNA, the existing simulated peroxidase catalytic efficiency, high cost and complex preparation problems are solved, and the effect of significantly enhancing peroxidase activity and reducing cost is achieved.

CN119500272APending Publication Date: 2025-02-25NAT UNIV OF DEFENSE TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411646259.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing catalytic efficiency of simulated peroxidase has not yet reached the expected level, and the use of precious metals has high costs, the preparation process is complex and requires high temperatures, which limits its wide application.

Method used

Using the metal-porphyrin derivative organic framework structure and G-DNA composite material, the MOF-DNA composite material with excellent peroxidase activity is synthesized by controlling the molar ratio of porphyrin derivatives to metals.

Benefits of technology

The peroxidase activity is enhanced by 7-17 times, reducing costs, avoiding high-temperature reaction conditions, simplifying the preparation process, and improving catalytic efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500272A_ABST
    Figure CN119500272A_ABST
Patent Text Reader

Abstract

The invention relates to an MOF-DNA composite material as well as a preparation method and application thereof. The MOF-DNA composite material comprises a metal-porphyrin derivative organic framework structure, and G-DNA is compounded on the metal-porphyrin derivative organic framework structure; wherein the porphyrin derivative is a porphyrin derivative containing Fe. The MOF-DNA composite material disclosed by the invention has very excellent peroxidase activity, and a metal-porphyrin derivative organic frame structure and G-DNA have a mutual synergistic effect, so that the peroxidase activity can be greatly enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a MOF-DNA composite material, a preparation method and application thereof. Background Art

[0002] Nanozyme is a new type of artificial enzyme mimic that combines the catalytic activity of natural enzymes with the unique properties of nanomaterials. Compared with natural enzymes, it has the advantages of good stability, low cost, and scalability.

[0003] Metal organic frameworks are a type of porous material with a periodic network structure formed by the interconnection of inorganic metal centers (metal ions or metal clusters) and bridging organic ligands through self-assembly. MOF can be effectively designed as a biomimetic enzyme. To date, more than 20 different metal-centered MOF-based enzymes have been reported. They exhibit enzyme catalytic activities such as peroxidase, oxidase, and superoxide dismutase, and are widely used in various fields. Currently, researchers have developed a variety of MOF-based nanomaterials with peroxidase-like catalytic activity.

[0004] For example, Chen Ligang et al. (A method for preparing nanogold composite bimetallic organic framework nanozymes and their application of peroxidase activity: CN202211257434.0[P].2023-04-07) used 2-aminoterephthalic acid as a ligand, synthesized bimetallic organic framework nanozymes by solvothermal method (110-130°C), and then in situ grew nanogold on the surface of the material to prepare nanogold composite bimetallic organic framework composite materials with peroxidase activity. Li Jian et al. (Cascade nanozymes and their preparation methods and applications: CN202211142374.8[P].2023-03-1) used two-dimensional metal organic framework peroxidase mimetic nanosheets formed by metal salts and ligands as carriers, and bound gold nanoparticles (AuNPs) to the surface of peroxidase mimetic nanosheets through electrostatic attraction to form artificial nanozymes. Zhang Xiaomei et al. (A polymer, its preparation method and its application as bacterial detection and antibacterial material: CN201910881140.7[P].2020-01-21) used pyrrole and compound BFPB as raw materials and synthesized a porous organometallic polymer with good peroxidase-like activity by a hydrothermal method (170-190°C).

[0005] Although existing peroxidase mimics have made progress in catalytic efficiency, they still face some challenges: the catalytic efficiency has not yet reached the expected level, the use of precious metals has led to high costs, and the preparation process is complicated, often requiring heating or high temperatures, which makes the cost and time investment relatively high. These factors together limit their widespread application. Summary of the invention

[0006] In view of the deficiencies of the prior art, one of the objects of the present invention is to provide a MOF-DNA composite material with excellent peroxidase activity; a second object of the present invention is to provide a method for preparing a MOF-DNA composite material; a third object of the present invention is to provide an application of a MOF-DNA composite material.

[0007] In order to solve the above technical problems, the technical solution of the present invention is as follows:

[0008] A MOF-DNA composite material comprises a metal-porphyrin derivative organic framework structure, on which G-DNA is composited; wherein the porphyrin derivative is a porphyrin derivative containing Fe.

[0009] Furthermore, the G-DNA is a DNA rich in guanine. Still further, the guanine content in the G-DNA (i.e. the percentage of guanine in the total number of bases in the G-DNA) is greater than 50%, preferably 55-75%.

[0010] Further, the G-DNA is a G-quadruplex DNA; preferably, the sequence of the G-DNA is F3TC (TTTGGGTGGGTGGGTGGGTC) or Pw17a (GGGTAGGGCGGGTTGGGA). Guanine quadruplex (G4) is a unique nucleic acid secondary structure, and the G4-DNA sequence can bind to metals, dyes, porphyrins, etc., and exhibits oxidase-like catalytic activity.

[0011] Furthermore, the porphyrin derivative is hemin chloride.

[0012] Furthermore, the metal is copper.

[0013] Furthermore, in the metal-porphyrin derivative organic framework structure, the molar ratio of the porphyrin derivative to the metal is 1:90-500, preferably 1:100-350, and more preferably 1:105-300. The applicant has found through in-depth research that controlling the molar ratio of the porphyrin derivative to the metal can help further improve the peroxidase activity of the MOF-DNA composite material.

[0014] The preparation method of the MOF-DNA composite material as described above comprises the following steps:

[0015] S1, mixing a porphyrin derivative solution and a metal salt solution, and after the reaction, performing solid-liquid separation, washing, and drying to obtain a metal-porphyrin derivative organic framework material;

[0016] S2. Incubate the metal-porphyrin derivative organic framework material and G-DNA in an aqueous solution to obtain a MOF-DNA composite material.

[0017] In this way, the synthesized metal-porphyrin derivative organic framework material has a structure similar to porphyrin and can bind to G-DNA. The resulting MOF-DNA composite material has outstanding peroxidase activity.

[0018] Further, in S1, the porphyrin derivative solution and the metal salt solution are mixed at a volume ratio of 1:0.5-1.5, preferably, the porphyrin derivative solution and the metal salt solution are mixed at a volume ratio of 1:0.75-1.25;

[0019] Preferably, the concentration of the porphyrin derivative solution is 0.2-1 mmol / L, more preferably 0.4-0.8 mmol / L;

[0020] Preferably, the concentration of the metal salt solution is 10-100 mmol / L, more preferably 20-90 mmol / L;

[0021] Preferably, the metal salt is copper nitrate or copper nitrate trihydrate;

[0022] Preferably, in S1, the molar ratio of the porphyrin derivative to the metal is 1:90-500, preferably 1:100-350, and more preferably 1:105-300.

[0023] Further, in S1, the reaction temperature is controlled to be 20-40°C, preferably room temperature;

[0024] Preferably, the reaction time is 20-40 h, more preferably 25-35 h.

[0025] Further, in S2, the mixture is incubated at 20-40° C. and a neutral pH value for 10-50 min.

[0026] Furthermore, in S2, the metal-porphyrin derivative organic framework structure material is prepared into a 0.05-0.15 mg / ml MOF solution, and the G-DNA is prepared into a 8-12 μM DNA solution; the MOF solution and the DNA solution are then mixed and incubated to obtain a MOF-DNA composite material.

[0027] Application of the MOF-DNA composite material as described above or the MOF-DNA composite material prepared by the preparation method as peroxidase.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] (1) The MOF-DNA composite material of the present invention has very excellent peroxidase activity. The metal-porphyrin derivative organic framework structure and G-DNA interact synergistically to greatly enhance the peroxidase activity. Compared with the independent metal-porphyrin derivative organic framework structure or G-DNA, the peroxidase activity of the MOF-DNA composite material of the present invention can be enhanced by 7-17 times.

[0030] (2) The preparation method of the present invention does not require the use of precious metals, has low cost, and does not require heating and high-temperature reaction conditions. It can be carried out at low temperature or even room temperature, and a product with high peroxidase activity is obtained. The synthesis process is very simple. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 It is the XRD spectrum of the copper-hemin organic framework material and hemin of Example 1 of the present invention.

[0032] Figure 2 It is the UV-visible absorption spectrum of Application Example 1 and Comparative Examples 1-3.

[0033] Figure 3 This is a graph showing the absorbance detection results of Application Example 2-4.

[0034] Figure 4 This is a graph of absorbance detection results of Example 3-12, wherein the abscissa is the amount of DNA aqueous solution added.

[0035] Figure 5 This is a schematic diagram of the preparation process of the copper-hemin organic framework material of Example 1.

[0036] Figure 6 Schematic diagram of the incubation process of Example 1 and the detection process of Application Example 1.

[0037] Figure 7 This is the SEM image of the copper-hemin organic framework material obtained in Example 1. DETAILED DESCRIPTION

[0038] The present invention will be described in detail below in conjunction with the embodiments. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.

[0039] Example 1

[0040] The preparation method of the MOF-DNA composite material of this embodiment comprises the following steps:

[0041] S1. Mixing the hemin solution and the copper nitrate solution in a volume ratio of 1:1, reacting, separating the solid from the liquid, washing, and drying to obtain a copper-hemin organic framework material (Cu-hemin, whose XRD pattern is shown in Figure 1 , its SEM image is shown in Figure 7 );

[0042] Among them, the concentration of hemin chloride solution is 0.25mmol / L; the concentration of copper nitrate solution is 26.25mmol / L;

[0043] S2. The copper-hemin organic framework material is prepared into a 0.1 mg / ml MOF aqueous solution (dispersion), and the G-DNA with a sequence of F3TC is prepared into a 10 μmol / L DNA aqueous solution; then 10 μL of the MOF aqueous solution and 10 μL of the DNA aqueous solution are mixed, and after incubation, a MOF-DNA composite material is obtained.

[0044] In S1, the reaction temperature was controlled to be room temperature and the reaction time was 24 h. In S2, the reaction was incubated for 30 min at room temperature and a neutral pH value.

[0045] Application example 1 (G4+Cu-hemin)

[0046] To all MOF-DNA composite materials obtained by S2 in Example 1, 30 μL of TMB (3,3',5,5'-tetramethylbenzidine) solution (concentration 1 mM) was added, and acetic acid-sodium acetate buffer (0.2 mol / L) with a pH of 4.4 was added to make the total volume of the reaction system 200 μL, and finally 30 μL of H2O2 solution (concentration 25 mM) was added. Then, the absorption spectrum (600-700 nm, specifically at 652 nm) was immediately detected by ultraviolet spectrophotometer, and the peroxidase activity performance of the MOF-DNA composite material was studied according to the strength of the absorption signal.

[0047] Comparative Example 1 (Cu-hemin)

[0048] Application Example 1 was repeated, with the only difference being that all of the MOF-DNA composite materials obtained in S2 of Example 1 were replaced by 10 μL of the MOF aqueous solution described in Example 1.

[0049] Comparative Example 2 (G4)

[0050] Application Example 1 was repeated, with the only difference being that 10 μL of the DNA aqueous solution described in Example 1 was used to replace all of the MOF-DNA composite materials obtained in S2 of Example 1.

[0051] Comparative Example 3 (Control)

[0052] Application Example 1 was repeated, with the following difference: acetic acid-sodium acetate buffer with pH = 4.4 was added directly to 30 μL of TMB solution (concentration 1 mM) to make the total volume of the reaction system 200 μL, and finally 30 μL of H2O2 solution (concentration 25 mM) was added.

[0053] Figure 2 The absorption signal spectra of Application Example 1 and Comparative Examples 1-3 show that the peroxidase activity of the MOF-DNA composite material is significantly better than that of Cu-hemin and G4 when used alone, and higher than the sum of the two when used alone, showing a significant synergistic effect.

[0054] Application Example 2 (Cu-hemin+F3TC)

[0055] To all MOF-DNA composite materials obtained in S2 in Example 1, 40 μL Mes-tris buffer (pH=5.5), 120 μL H2O, 10 μL ABTS solution, and finally 10 μL H2O2 (25 mM) were added.

[0056] The absorbance (425 nm) was detected using a multi-function microplate reader.

[0057] Example 2

[0058] Example 1 was repeated, except that the sequence of the G-DNA was Pw17a.

[0059] Application example 3 (Cu-hemin+pw17a)

[0060] Application Example 2 was repeated, with the only difference being that all the MOF-DNA composite materials obtained in S2 of Example 2 were used to replace all the MOF-DNA composite materials obtained in S2 of Example 1.

[0061] Application example 4 (Cu-hemin)

[0062] Application Example 2 was repeated, with the only difference being that all of the MOF-DNA composite materials obtained in S2 of Example 1 were replaced by 10 μL of the MOF aqueous solution described in Example 1.

[0063] Figure 3 This is a graph of absorbance detection results of Application Example 2-4. It can be seen from the figure that the absorbance of the MOF-DNA composite material of the present invention is significantly higher than that of the copper-hemin organic framework material, and when the sequence of G-DNA is F3TC, the improvement of absorbance is particularly obvious.

[0064] Example 3-7 (F3TC)

[0065] Example 1 was repeated, except that 5 μL of MOF aqueous solution was mixed with 5 μL (Example 3), 10 μL (Example 4), 15 μL (Example 5), 20 μL (Example 6) or 25 μL (Example 7) of DNA aqueous solution. The absorbance was detected according to the method described in Application Example 7.

[0066] Example 8-12 (Pw17a)

[0067] Example 2 was repeated, except that 5 μL of MOF aqueous solution was mixed with 5 μL (Example 8), 10 μL (Example 9), 15 μL (Example 10), 20 μL (Example 11) or 25 μL (Example 12) of DNA aqueous solution. The absorbance was detected according to the method described in Application Example 7.

[0068] Figure 4 The absorbance detection result diagram of Example 3-12 shows that when the sequence of G-DNA is F3TC, the absorbance performance is particularly outstanding, and the relevant effect is significantly better than when the sequence of G-DNA is Pw17a. In addition, when the sequence of G-DNA is F3TC, the addition ratio of MOF aqueous solution to DNA aqueous solution is controlled at 5μL:5-15μL, and the absorbance is particularly outstanding.

[0069] The contents explained in the above embodiments should be understood as these embodiments are only used to more clearly illustrate the present invention, and are not used to limit the scope of the present invention. After reading the present invention, various equivalent forms of modifications to the present invention by those skilled in the art all fall within the scope defined by the claims attached to this application.

Claims

1. A MOF-DNA composite material, characterized in that: It comprises a metal-porphyrin derivative organic framework structure, on which G-DNA is compounded; wherein the porphyrin derivative is a porphyrin derivative containing Fe.

2. The MOF-DNA composite material according to claim 1, characterized in that The G-DNA is a guanine-rich DNA. Preferably, the G-DNA is a G-quadruplex DNA. Preferably, the sequence of the G-DNA is F3TC or Pw17a.

3. The MOF-DNA composite material according to claim 1, characterized in that: In the metal-porphyrin derivative organic framework structure, the molar ratio of the porphyrin derivative to the metal is 1:90-500, preferably 1:100-350, more preferably 1:105-300. Preferably, the porphyrin derivative is hemin chloride.

4. The MOF-DNA composite material according to claim 1, characterized in that: The metal is copper.

5. The method for preparing the MOF-DNA composite material according to any one of claims 1 to 4, characterized in that: The steps include: S1, mixing a porphyrin derivative solution and a metal salt solution, and after the reaction, performing solid-liquid separation, washing, and drying to obtain a metal-porphyrin derivative organic framework material; S2. Incubate the metal-porphyrin derivative organic framework material and G-DNA in an aqueous solution to obtain a MOF-DNA composite material.

6. The preparation method according to claim 5, characterized in that: In S1, the porphyrin derivative solution and the metal salt solution are mixed at a volume ratio of 1:0.5-1.5, preferably, the porphyrin derivative solution and the metal salt solution are mixed at a volume ratio of 1:0.75-1.25; Preferably, the concentration of the porphyrin derivative solution is 0.2-1 mmol / L, more preferably 0.4-0.8 mmol / L; Preferably, the concentration of the metal salt solution is 10-100 mmol / L, more preferably 20-90 mmol / L; Preferably, the metal salt is copper nitrate or copper nitrate trihydrate; Preferably, in S1, the molar ratio of the porphyrin derivative to the metal is 1:90-500, preferably 1:100-350, and more preferably 1:105-300.

7. The preparation method according to claim 5, characterized in that: In S1, the reaction temperature is controlled to be 20-40°C, preferably room temperature; Preferably, the reaction time is 20-40 h, more preferably 25-35 h.

8. The preparation method according to claim 5, characterized in that: Incubate in S2 at 20-40°C and neutral pH for 10-50 min.

9. The preparation method according to claim 5, characterized in that: In S2, the metal-porphyrin derivative organic framework structure material is prepared into a 0.05-0.15 mg / ml MOF solution, and the G-DNA is prepared into a 8-12 μM DNA solution; then the MOF solution and the DNA solution are mixed at a volume ratio of 1:0.5-1.5, and after incubation, a MOF-DNA composite material is obtained.

10. Use of the MOF-DNA composite material according to any one of claims 1 to 4 or the MOF-DNA composite material prepared by the preparation method according to any one of claims 5 to 9 as a peroxidase.

Citation Information

Patent Citations

  • A polymer, its preparation method, and its application as a material for detecting bacteria and for antimicrobial purposes.

    CN110713603B

  • Cascaded nano-enzyme as well as preparation method and application thereof

    CN115779971A